2021
DOI: 10.1017/s0022215121001146
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional printed myringotomy, tympanostomy and ventilation tube placement simulator

Abstract: Objective Tympanostomy is one of the most commonly performed surgical procedures in otolaryngology, and its complexity is challenging for trainee surgeons. Investing in medical education is a cornerstone of good patient safety practices. For trainees, use of simulators before operating on actual patients helps mitigate risks. This study aimed to develop a three-dimensional printed model simulator for myringotomy, tympanostomy and ventilation tube placement. Methods An articulated model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…The advantages of using prototypes include portability, since they allow trainees' movements to different locations, and the possibilities of commercialization and wide distribution. A comparison of the 3D approach and animal and cadaver models highlights ethical discussions, workspace limitations, acquisition difficulties, and biological risks [32,41]. Furthermore, cadaver models/pieces have limited availability and incur high costs.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of using prototypes include portability, since they allow trainees' movements to different locations, and the possibilities of commercialization and wide distribution. A comparison of the 3D approach and animal and cadaver models highlights ethical discussions, workspace limitations, acquisition difficulties, and biological risks [32,41]. Furthermore, cadaver models/pieces have limited availability and incur high costs.…”
Section: Discussionmentioning
confidence: 99%
“…On the printed model created based on CT of the patient’s temporal bones, the surgeon can plan operations and practice its separate stages, which improves the quality of treatment. In addition, 3D models of the external auditory canal and the tympanic membrane enabled students and younger residents in otolaryngology to perform tympanic membrane paracentesis and insert the ventilation drainages to the tympanic cavity before real-life procedures [ 78 ]. Frendo et al, in their study, observed a shortening of the learning curve among otosurgeons who used 3D models of the temporal bones in the education process of cochlear implant surgery.…”
Section: Discipline Specific Applicationsmentioning
confidence: 99%
“…Simuladores permitem o aprimoramento da capacidade cognitiva, modulam o ensino por etapas e por tarefas, e pode otimizar o processo de aprendizagem. A otologia tem se destacado dentro da otorrinolaringologia como o principal usuário de simuladores virtuais e físicos [26] .…”
Section: História Da Simulação Cirúrgica E Métodos De Treinamentounclassified